Women's Obstetric History and Midtrimester Cervical Length Measurements by 2D/3D and Doppler Ultrasound - Juliana Valente Codato Marinelli; Antonio Gomes de Amorim Filho; Monica Fairbanks de Barros; Agatha Sacramento Rodrigues; Rossana Pulcineli Vieira Francisco; Mario Henrique Burlacchini de Carvalho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective The aim of the present study was to compare the obstetric history and both two- and tri-dimensional ultrasound parameters according to different cervical lengths. Methods The present cross-sectional study analyzed 248 midtrimester pregnant women according to cervical length and compared the data with the obstetric history and 2D/3D ultrasound parameters. Patients were divided into 3 groups according to cervical length: The Short Cervix group for cervical lengths ≥ 15mm and< 25mm(n= 68), the Very Short Cervix group for cervical lengths< 15mm (n = 18) and the Control group, composed of 162 pregnant women with uterine cervical lengths ≥ 25mm. Results When analyzing the obstetric history of only non-nulliparous patients, a significant association between the presence of a short cervix in the current pregnancy and at least one previous preterm birth was reported (p = 0.021). Cervical length and volume were positively correlated (Pearson coefficient = 0.587, p < 0.0001). The flow index (FI) parameter of cervical vascularization was significantly different between the Control and Very Short Cervix groups. However, after linear regression, in the presence of volume information, we found no association between the groups and FI. Uterine artery Doppler was also not related to cervical shortening. Conclusion The present study showed a significant association between the presence of a short cervix in the current pregnancy and at least one previous preterm birth. None of the vascularization indexes correlate with cervical length as an independent parameter. Uterine artery Doppler findings do not correlate with cervical length.